Decadal variation of the relationship between the previous autumn IOD and the South China Sea summer monsoon - Zheng, Meiying; Xu, Feng; Liu, Shengyuan; Li, Yongchi; Zhang, Shaojing; Yang, Jinyi (Frontiers in Earth Science, 2023)
The relationship between Indian Ocean Dipole (IOD) in the previous autumn (September-November) and South China Sea Summer (June-August) Monsoon (SCSSM) was significantly enhanced from the late 70s to the beginning of the 21st century (P2), with a significant resonance cycle of 2-4a. The previous autumn IOD forced the Gill pattern in the upper troposphere by changing the Sea Surface Temperature Anomaly (SSTA) of the following summer in the Tropical Indian Ocean (TIO), resulting in the anticyclonic circulation anomaly in the Philippine Sea. It eventually alters the southwest monsoon near the South China Sea and the Philippine Sea. However, as PDO turns from warm to cold, the relationship between El Niño–Southern Oscillation (ENSO) and IOD weakens, the impact of the previous autumn IOD on Indian Ocean SSTA in the summer of the following year weakens, resulting in a decrease in the correlation between the previous autumn IOD and SCSSM. The impact of the previous autumn's Indian Ocean SSTA on the following year's SCSSM is more considered in terms of the eastern Bay of Bengal and the Somali Sea basin. In addition, during the warm phase of PDO, the IOD of the previous autumn can cause abnormal summer precipitation in South China by strengthening or weakening the Western Pacific Subtropical High (WPSH) of the following summer, but there is no significant effect in the cold phase of PDO.